Female entrepreneurship in the technological sector: Challenges and strategies for overcoming gender barriers (Research, Society and Development, 2025)
This article aims to investigate and analyze the landscape of female entrepreneurship in the technology sector, identifying advances, challenges, and unique contributions. The central objective of this article is to analyze the main challenges faced by women entrepreneurs in the Brazilian technology sector and identify strategies employed to overcome gender barriers. The research aims to provide a critical overview for reflection and improvement of policies aimed at gender equity in innovation. To conduct this study, a systematic literature review methodology was employed. This method involved the search and careful analysis of scientific articles, reports, and other relevant sources in academic databases. The selection of materials was guided by criteria of timeliness and relevance, seeking to compile and synthesize meaningful information on the topic. The analysis allowed us to identify recurring patterns, trends, and challenges. The results indicate an increase in female participation, with more women founding startups. However, significant barriers persist, especially in accessing funding, forming networks, and overcoming prejudices. Underrepresentation in decision-making positions and cultural stereotypes were identified as limiting factors. Despite this, female entrepreneurship stands out as a driver of innovation and creativity. The conclusion is that promoting gender equality is fundamental to economic development and innovation. Limitations include the reliance on secondary data and the rapid evolution of the sector. Recommendations are made for future qualitative, longitudinal, and policy-focused research on intra-gender diversity.